Rice, Relics, and Jewels: The Network and Agency of Rice Grains in Medieval Japanese Esoteric Buddhism - Trenson, Steven (Japanese journal of religious studies, 2018)
Rice fulfilled an important sacred function in medieval Japanese esoteric Buddhist practice and worship. Its religious use was primarily based on Buddhist doctrines establishing a connection between rice grains and relics of the Buddha, but there were also other, non-canonical beliefs that further enhanced the religious value of the grains. The present article first explains some of the basic Buddhist scriptural doctrines and then proceeds with a discussion of the historical networks in which these doctrines continued to develop in medieval Japan. Attention is given to the "agency" of rice in order to determine what effect rice grains had on the development of correlated Japanese esoteric Buddhist thought and conceptualizations and on the formation of some remarkable new religious objects, rituals, doctrines, and iconographies. In this way, the article aims to illustrate how rice, as an influential factor or agent, helped to shape the landscape of religion in premodern Japan.